Factors affecting GDI improvement after single event multilevel surgery in patients with cerebral palsy - Min, Jae Jung; Kwon, Soon Sun; Sung, Ki Hyuk; Lee, Kyoung Min; Chung, Chin Youb; Park, Moon Seok (Gait and Posture, 2020)
Background: Pathologic gait is common in patients with cerebral palsy (CP). Single-event multilevel surgery (SEMLS) is a combination of surgical procedures to improve pathologic gait in patients with CP. However, the effect of each procedure is difficult to predict. The gait deviation index (GDI) is useful in comparing pre- and postoperative improvement. Research question: In this study, we evaluated the degree of GDI improvement in patients with CP and analyzed factors related to surgical outcomes. Methods: We screened patients seen between May 2003 and December 2019 via a clinical data warehouse to identify those with CP who had been followed up for >1 year and who had undergone SEMLS. The inclusion criteria were (1) CP patients with GMFCS levels I, II and III, (2) patients who underwent SEMLS, (3) and patients who underwent 3D gait analyses preoperatively and at least 1 year postoperatively. A linear mixed model was used to model GDI improvement, assess effects of covariates, and examine factors that contributed to improvement. Results: Overall, 544 patients were included. The average improvement in overall GDI was 8.9 ± 12.3, 9.6 ± 12.0, and 6.4 ± 8.6 in Gross Motor Function Classification System (GMFCS) levels I, II, and III, respectively. In GMFCS level II patients, GDI improvement decreased by 0.26 points with a 1-year delay in surgery (p = 0.0022). Within each group of GMFCS levels, femoral derotation osteotomy (FDO) was a significant factor in GDI improvement in GMFCS levels I and II. Rectus femoris transfer (RFT) and supracondylar extension osteotomy (SCO) were significant factors in GMFCS level II. No single procedure was shown to affect improvement in GMFCS level III. Significance: Postoperative GDI improved in all levels of GMFCS. Particular procedures especially affected postoperative improvement in GDI in levels I and II. Our data do not mean to set an indication for particular procedures; however, in GMFCS levels I, II patients, particular procedures, such as FDO, yielded a greater GDI improvement in our data set.
Keywords: Adolescent; Cerebral Palsy; Child; Child, Preschool; Female; Femur; Gait Analysis; Gait Disorders, Neurologic; Humans; Male; Osteotomy; Postoperative Period; Quadriceps Muscle; Retrospective Studies; Treatment Outcome; Cerebral palsy; GDI; GMFCS; SEMLS